PENINGKATAN HASIL BELAJAR MATERI INDUKSI MAGNET MELALUI MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION PADA SISWA KELAS XII MIA 3 SMAN 2 PONTIANAK - Udzaenah, Udzaenah (Jurnal Kajian Pembelajaran dan Keilmuan, 2018)
AbstractThis research was aimed to increase student’s achievement of XII MIA 3 students of SMA Negeri 2 Pontianak on magnetic induction materials. This research consist of 2 (two) cycles with each meeting takes time 3x45 minutes. Each cycle consisted of planning,  implementation,  observation,  and  analysis  section.To  know  class management, teacher and student;s observation sheet was used.The results showed that application of cooperative learning model Team Assisted Individualization can improve student’s achievement in class XII MIA 3 SMA Negeri 2 Pontianak on magnetic induction material. It can be seen from the increase in average grade from 67.9 to 76.32 and the percentage of students who pass the tes rosefrom 52.63% in the first cycle becomes 76.32% in the second cycle. Kata kunci: Induksi Magnet, Hasil Belajar, Team Assisted Individualization